Hybrid carbon/glass fiber composites: Micromechanical analysis of structure–damage resistance relationships - Mishnaevsky, Leon; Dai, Gaoming (Computational materials science, 2014)
•Damage evolution of hybrid carbon/glass fiber composites (HC) is studied.•Hybrid composites can have lower strength than (less stiff) pure glass composites.•Critical elongation of HC decreases with increasing the fraction of carbon fibers.•The results obtained from the fiber bundle model are validated by 3D FEM model. A computational study of the effect of microstructure of hybrid carbon/glass fiber composites on their strength is presented. Unit cells with hundreds of randomly located and misaligned fibers of various properties and arrangements are subject to tensile and compression loading, and the evolution of fiber damages is analyzed in numerical experiments. The effects of fiber clustering, matrix properties, nanoreinforcement, load sharing rules on the strength and damage resistance of composites are studied. It was observed that hybrid composites under uniform displacement loading might have lower strength than pure composites, while the strength of hybrid composites under inform force loading increases steadily with increasing the volume content of carbon fibers.